2004
DOI: 10.1021/ja049493o
|View full text |Cite
|
Sign up to set email alerts
|

High Velocity Interparticle Collisions Driven by Ultrasound

Abstract: During bubble collapse, intense shock waves are generated and propagate through the liquid at velocities above the speed of sound. [1][2][3][4] Unusual sonochemical effects are induced by these shock waves, most importantly, high velocity collisions among solid particles suspended in such liquids. 4 These collisions result in extreme heating at the point of impact, which can lead to effective local melting and dramatic increases in the rates of many solid-liquid reactions. [5][6][7][8] In this work, we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(124 citation statements)
references
References 10 publications
2
122
0
Order By: Relevance
“…[77,81] However, the Co-B particle size increased with increasing US power and sonication time due to the melting agglomeration. [24] Thus, optimal sonication conditions ensured the preparation of a catalyst with superior performance, which had a significantly greater metallic area and better Co-B particle dispersion and Co active sites. It was proved that the US-prepared Co-B catalyst exhibited much higher activity than the regular Co-B obtained via the direct reduction of Co 2+ with BH4 -for liquid-phase CMA reduction.…”
Section: Co-catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[77,81] However, the Co-B particle size increased with increasing US power and sonication time due to the melting agglomeration. [24] Thus, optimal sonication conditions ensured the preparation of a catalyst with superior performance, which had a significantly greater metallic area and better Co-B particle dispersion and Co active sites. It was proved that the US-prepared Co-B catalyst exhibited much higher activity than the regular Co-B obtained via the direct reduction of Co 2+ with BH4 -for liquid-phase CMA reduction.…”
Section: Co-catalystsmentioning
confidence: 99%
“…[18] Sonication can also inhibit particle aggregation thanks to the intense implosion of acoustic cavitation. [21][22][23][24] The US-assisted chemical reduction method has been successfully applied in the preparation of amorphous alloys with homogeneous particle size. [25] When a cavitation bubble violently collapses near a solid surface, the high-speed jets of liquid are driven into the surface of a particle.…”
Section: Introductionmentioning
confidence: 99%
“…The cavitation phenomenon is the largest nonthermal effect created by ultrasound energy (Doktycz and Suslick, 1990;Prozorov et al, 2004). Cavitation is considered to be a main mechanism for causing alterations to biological tissues, especially increased membrane permeability (Sivakumar et al, 2005).…”
Section: Acoustic Cavitationmentioning
confidence: 99%
“…This collapse of cavitations is accompanied by a high release of energy, which itself produces local sound waves with pressures of hundreds of atmospheres and transient hot spots with temperatures of several thousand K (Gedanken, 2004). It was also reported that shock waves generated by cavitations in liquids containing metal particles drives the particles together at extremely high speeds, causing a series of unavoidable collisions among the particles (T. Prozorov, R. Prozorov, & Suslick, 2004). This results in severe destruction of the particles and forces large grains into fragments of particles and grains of smaller sizes.…”
Section: Effects Of Sintering Temperature On the Mean Crystallite Sizementioning
confidence: 99%